Identifying Measurable Impact of Islamic Banking on the Indonesian Economy - Haryani Santo Hartono; Rininta Nurrachmi (Etihad: Journal of Islamic Banking and Finance, 2025)
Introduction: This study investigates the short- and long-term relationship between Islamic banking development and Indonesia’s economic growth. Despite Indonesia operating a dual banking system, empirical research on Islamic finance and growth remains limited. Understanding this connection is crucial for leveraging Islamic finance as a driver of sustainable development. Research Methods: Using quarterly data from 2015 to 2024, the study examines the dynamic links among Islamic financing, GDP, and gross fixed capital formation (GFCF). The ARDL bounds testing approach, cointegration analysis, and error correction model (ECM) are employed to identify both short- and long-run relationships. Model stability is validated using CUSUM and CUSUMSQ tests. Results: The results reveal a strong long-term relationship between Islamic financial development, capital accumulation, and economic growth, supporting the supply-leading hypothesis. Short-term effects are positive but statistically insignificant. Model stability tests confirm structural consistency over time. Conclusion: These findings emphasize the potential of Islamic finance to promote sustainable economic development and provide guidance for policymakers seeking to enhance financial inclusion and resilience.